Spatial distribution of obesity, its predisposing factors and associated complications at the Dimamo Population Health Research Centre, Limpopo Province, South Africa - Ntimana, Cairo Bruce (My University, 2023)
Introduction: Obesity is a physical condition resulting from excessive fat storage in the body. Globally at least 2.8 million people die due to being overweight and obesity. Changes in life habits and patterns, such as dietary behaviors, advances in technology, beliefs, sedentary life, and a decrease in physical activities, increases obesity and weight gain among men and women Obesity has also been associated with socioeconomic status. The prevalence of spatial distribution of obesity and overweight has been shown to be high in urban areas and wealthier regions of the country. Purpose: To profile obesity in terms of spatial distribution, new classifications, measurements of predisposing factors, and associated complications at DIMAMO Population Health Research Centre (PHRC), Limpopo Province, South Africa. Methodology: This was a cross-sectional, retrospective study. The present study used secondary data from the AWI-Gen phase 1 study. The present study analysed 791 participants (242 males and 459 females). Data were analysed using the Statistical Package for Social Sciences version 27. Results: The present study's findings showed a high proportion of obesity (35.4%) and central obesity (59.9%). The proportion of healthy obese by high BMI in the total population was 22.9% and the proportion of healthy obese by high WC in the total population was 23.6%. Obesity correlated negatively with smoking, alcohol consumption, single, and divorced status, and also correlated positively associated with married status. Central obesity correlated negatively with smoking, and also correlated positively associated with married status, and being unemployed. The prevalence of obesity and central obesity was significantly higher in cluster A and B as compared to other clusters. Spatial distribution of general obesity and central obesity correlated with gender, smoking alcohol, consumption and married status Conclusion: The prevalence of obesity and central obesity were both high in the study population. Obesity and central obesity were more common in the North-eastern villages clusters compared to the Western and Southern clusters> The distribution of Obesity seems to be determined by gender, smoking alcohol, consumption and married status.
Thesis (M.Sc. (Medical Sciences)) -- University of Limpopo, 2024
Keywords: Obesity; Central obesity; VAT; SAT; Socio-demographic profiles; Obesity -- Social aspects; Obesity -- Treatment; Obesity -- Prevention; Overweight persons; Body mass index